Generation mean analysis of kernel iron and zinc concentrations in maize (Zea mays) - CHAKRABORTI, M; PRASANNA, B M; SINGH, ANJU M; HOSSAIN, F (The Indian Journal of Agricultural Sciences, 2010)
Alleviating micronutrient malnutrition through biofortification of food crops is an important objective of breeding programmes. Of particular importance is breeding for micronutrient enrichment, especially iron and zinc in crops, like maize (Zea mays L.). In the present study, generation mean analysis was undertaken for the first time to estimate the nature and magnitude of gene effects for kernel iron and zinc concentrations in 2 specific crosses of maize, with contrasting parental lines. Scaling test indicated the influence of epistasis on the expression of both micronutrients and inadequacy of additive-dominance model to explain the variation in different generations. Similar types of components of gene action for a particular micronutrient were observed, albeit some differences in the direction and magnitude of effects. Additive gene action was of higher magnitude as compared to dominance for kernel iron, while dominance was relatively higher in case of kernel zinc. Additive×dominance component was significant in both the crosses for kernel Fe, whereas additive×additive component was predominant for kernel zinc. Different non-additive components acted in opposite directions in both the crosses for kernel Fe, which could be a bottleneck to exploit heterosis. Recurrent selection and population improvement programmes, coupled with development of superior heterotic pools of inbred lines with enhanced kernel iron and zinc concentrations, could be effective in improving concentrations.